Carbamazepine Cardiotoxicity - J Gordon Millichap (Pediatric Neurology Briefs)
A 13-month-old boy with complex partial seizures complicating tuberous sclerosis developed a cardiac conduction abnormality and heart block during treatment with carbamazepine in a report from the University of Massachusetts Medical School, Worcester, MA.